Phenomenology Studies: The Practice of Sexual Education Applied by Indonesian Parents - Ellya Rakhmawati; Desi Maulia; Kartinah Kartinah; Charli Sitinjak (Journal of Nonformal Education, 2023)
Parents in Indonesia feel taboo in mentioning the name of the genitals and their functions scientifically. It is because parents were not aware in providing sexual education materials to their children. This study explores the practice of sexual education applied by Indonesian parents. The research was carried out in Semarang city's kindergarten to nine parents with early childhood children as subjects. The study used a phenomenological approach and qualitative research methods. Data were collected through in-depth interviews, and provided informed consent signed by the subject's parents to obtain information on how to teach children about gender differences, differences in genitalia and its function, and how to take care body, and so on. Triangulation of data sources was used to test this qualitative method’s credibility. Triangulation of data sources that researchers obtained from parents about knowledge and understanding of sexual education is as an effort to prevent sexual violence. The results showed that the application of sexual education by Indonesian parents was carried out through three contents, namely sexual education materials taught by parents, learning media for early childhood education, and barriers to the application of sexual education. However, this study has limitations because it didn’t involve father as subjects because of the work focus.